Analysis of osseodensification with two drill systems versus conventional technique for dental implants –A paired comparative ex vivo study - Rafaela Regina de Lima; Lara Rúbia Marques Nascimento; Barbara Magalhães Figueiredo Dias; Dhelfeson Willya Douglas-de-Oliveira; Rodrigo Richard da Silveira; Frederico Santos Lages (PLoS ONE, 2026)
Objective To compare conventional and osseodensification techniques assessing insertion/removal torque, stability (ISQ), maximum temperature, and bone structural alterations, as well as evaluating the performance of osseodensification with two bur systems: Densah®/Versah and Bone Reamer Drills®/WF. Methods Sixteen bovine ribs were prepared into standardized samples. Each bone block received three osteotomies using different techniques following manufacturers’ protocols: G1 – conventional burs; G2 – osseodensification with Densah®/Versah burs (VS); G3 – osseodensification with Bone Reamer Drills®/WF burs. Osteotomies were performed under irrigation with 0.9% saline at 4–6 °C. Heat generation was recorded with a thermocouple; torque was measured at implant insertion and removal; ISQ was obtained after implant insertion using Osstell ISQ positioned 2 mm from the SmartPeg at a 45º angle. The burs were weighed before and after perforations and analyzed by scanning electron microscopy (SEM). Bone samples also underwent SEM analysis after implant removal. Results The osseodensification groups exhibited increased insertion and removal torque values and bone compaction at the implant interface was observed. There was no significant increases in ISQ or maximum temperature compared to conventional drilling. No significant mass loss was observed in either systems. Conclusion Bone instrumentation with both osseodensification kits improved primary implant stability, demonstrating higher insertion and removal torque values than conventional drilling in type IV bone. No significant ISQ and temperature differences were found. SEM revealed compacted bone at the implant interface in the osseodensification groups. No significant mass changes were observed. Clinical relevance Results suggest that both techniques are safe and effective for clinical recommendation.